2013
DOI: 10.3402/gha.v6i0.19252
|View full text |Cite
|
Sign up to set email alerts
|

Administrative integration of vertical HIV monitoring and evaluation into health systems: a case study from South Africa

Abstract: BackgroundIn light of an increasing global focus on health system strengthening and integration of vertical programmes within health systems, methods and tools are required to examine whether general health service managers exercise administrative authority over vertical programmes.ObjectiveTo measure the extent to which general health service (horizontal) managers, exercise authority over the HIV programme's monitoring and evaluation (M&E) function, and to explore factors that may influence this exercise of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…"they don't pick up the errors, so they are not Program people; they're just punching numbers ... because for us from Programs you can very easily spot something that looks funny ... ... whereas someone who's just punching number; if they punch 1, 2, 3 … 1, 2, 3, 48 they won't necessarily think about the 48, whereas you would immediately realize that, that 48 can't be." (Informant in Program Management) This is consistent with the results from another South African case study [33]. The researchers assessed the degree to which general health service (horizontal) managers exercise authority over the HIV program's M&E function, namely, HIV data collection, collation, analysis and use.…”
Section: Empirical Findingssupporting
confidence: 60%
See 1 more Smart Citation
“…"they don't pick up the errors, so they are not Program people; they're just punching numbers ... because for us from Programs you can very easily spot something that looks funny ... ... whereas someone who's just punching number; if they punch 1, 2, 3 … 1, 2, 3, 48 they won't necessarily think about the 48, whereas you would immediately realize that, that 48 can't be." (Informant in Program Management) This is consistent with the results from another South African case study [33]. The researchers assessed the degree to which general health service (horizontal) managers exercise authority over the HIV program's M&E function, namely, HIV data collection, collation, analysis and use.…”
Section: Empirical Findingssupporting
confidence: 60%
“…The researchers assessed the degree to which general health service (horizontal) managers exercise authority over the HIV program's M&E function, namely, HIV data collection, collation, analysis and use. They found that compared to vertical managers, i.e., managers working in a disease-specific (HIV) position, horizontal managers had lower HIV M&E knowledge, and were more likely to produce HIV data but less likely to use it [33].…”
Section: Empirical Findingsmentioning
confidence: 99%
“…21,23,28,32,33,71,72 For example, in South Africa, as a result of deconcentration from the National Department of Health to local departments, and devolution from national to local governments, health services were then accountable to both local and national government which led to confusion about priority setting and planning. 20 …”
Section: Resultsmentioning
confidence: 99%
“…The failure to achieve optimal BP control in the study setting may be attributed to health system factors. First, a study showed that the vertical HIV programme was not administratively integrated with the horizontal general health system in South Africa [45]. Second, the quality of care study, which used a quantitative approach, showed that five of the eight priority domains of care in the integrated model were not associated with good quality care in the pilot facilities [6].…”
Section: Changes In Patients' Health Outcomes Attributable To the Intmentioning
confidence: 99%